CYBER-URBAN SPACE CONNECTIONS ON THE RISE OF LABOUR ACTIVISM: A CASE STUDY OF INDONESIAN METAL WORKERS’ FEDERATION KETERHUBUNGAN RUANG PERKOTAAN-MAYA DALAM AKTIVISME BURUH: STUDI KASUS FEDERASI SERIKAT PEKERJA METAL DI INDONESIA - Aulia Hadi (LIPI Press, 2015)
Abstract This paper argues that both urban and cyber activisms play significant roles in the labour movements in Indonesia after the reformation 1998. Exploring Federasi Serikat Pekerja Metal Indonesia (FSPMI)-Indonesian Metalworkers’ Federation, this paper is aimed at a better understanding of the interdependencies between the urban and cyber spaces for labour movements. More specific, how do labours engage in cyber-urban activism to establish their movements in order to gain their political leverages? Results highlight four issues: (a) the growing of militant labour movement in the recent urban space; (b) the emergence of urban industrial working class; (c) cyber-urban space is a political terrain for the state, the corporate, and the labours; and (d) one side of cyber-urban connection can generate, strengthen, weaken, or even kill the other side. Keywords: FSPMI, labour, movement, cyber, urban, activism Abstrak Tulisan ini berpendapat bahwa aktivisme perkotaan maupun maya sama-sama memiliki peran penting dalam gerakan buruh di Indonesia setelah reformasi 1998. Dengan mengeksplorasi Federasi Serikat Pekerja Metal Indonesia (FSPMI), tulisan ini bertujuan untuk lebih memahami saling ketergantungan antara ruang perkotaan dan ruang maya untuk gerakan buruh. Lebih spesifik, bagaimana buruh terlibat dalam aktivisme ‘perkotaan-maya’ untuk membangun gerakan mereka dalam memperjuangkan pengaruh politiknya? Hasil penelitian menggarisbawahi empat isu, yaitu: (a) tumbuhnya gerakan buruh militan di ruang kota masa kini; (b) munculnya kelas pekerja industri perkotaan; (c) ruang ‘perkotaan-maya’ adalah medan politik untuk negara, perusahaan, dan buruh; serta (d) satu sisi dari keterhubungan ruang ‘perkotaan-maya’ dapat menghasilkan, memperkuat, melemahkan, atau bahkan membunuh sisi lain. Kata kunci: FSPMI, buruh, gerakan, maya, perkotaan, aktivisme